Refractory Childhood Pemphigoid Successfully Treated with Rituximab. Issue 5 (28th December 2012) - Fuertes, Irene; Luelmo, Jesús; Leal, Lorena; Romaní, Jorge; Sánchez, Silvia; Mascaró, José M.
Abstract Bullous pemphigoid is an acquired autoimmune blistering disorder affecting mostly elderly people that is rare in children. There have been fewer than 100 cases of childhood bullous pemphigoid reported. Childhood bullous pemphigoid (CBP) generally has a good prognosis. Remission is usually achieved within several weeks to a few months, and relapses are rare, although refractory cases can occur, and the disease may be life threatening, particularly when lesions generalize. Herein we describe the case of an infant with severe CBP refractory to multiple treatments. In our case, therapy with azathioprine and intravenous immunoglobulin resulted in a slight clinical response, but only combined with high doses of prednisolone. Administration of rituximab led to a complete clinical response and allowed almost complete steroid tapering. There are no current guidelines indicating what doses and frequency of rituximab are safest or most effective in children with blistering diseases.